2018
DOI: 10.3390/rs10121880
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Landslide Activity on a Regional Scale Using Persistent Scatterer Interferometry at the Moselle Valley (Germany)

Abstract: Landslides are a major natural hazard which can cause significant damage, economic loss, and loss of life. Between the years of 2004 and 2016, 55,997 fatalities caused by landslides were reported worldwide. Up-to-date, reliable, and comprehensive landslide inventories are mandatory for optimized disaster risk reduction (DRR). Various stakeholders recognize the potential of Earth observation techniques for an optimized DRR, and one example of this is the Sendai Framework for DRR, 2015–2030. Some of the major be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…As areas where landslides occur are displayed as clusters in SAR amplitude images, spatial autocorrelation is a feasible approach to extract location of landslides [23]. Additionally, [66] applied Moran's I to identify clustered permanent scattering (PS) points and then distinguish various landslide activities. Accordingly, in this study, spatial autocorrelation was applied on the LR index images to extract spatial clusters of intensity change, where were the candidates of landslides.…”
Section: Object-based Feature Extractionmentioning
confidence: 99%
“…As areas where landslides occur are displayed as clusters in SAR amplitude images, spatial autocorrelation is a feasible approach to extract location of landslides [23]. Additionally, [66] applied Moran's I to identify clustered permanent scattering (PS) points and then distinguish various landslide activities. Accordingly, in this study, spatial autocorrelation was applied on the LR index images to extract spatial clusters of intensity change, where were the candidates of landslides.…”
Section: Object-based Feature Extractionmentioning
confidence: 99%
“…Approaches for the automatic detection of such irregular patterns in space and time have been developed already (Zhu et al, 2018), few also considering the interaction between geology and observed subsidence (Pratesi et el., 2016;North et al, 2017). While some approaches rely principally on the velocity estimates for clustering (Kalia, 2018;Aslan, 2020), other approaches consider the time series of the displacements for identifying different deformation regimes (Zhu et al, 2018). This information is particularly important for infrastructure analysis, as many factors may impact the deformation (e.g.…”
Section: State-of-the-artmentioning
confidence: 99%
“…The first articles of using Sentinel-l SAR data for landslide monitoring have been presented by Monserrat et al (2016) and Barra et al (2016). Recently, Kalia (2018) applied 66 Sentinel acquisitions in a descending orbit mode for classification of landslide activity on a regional scale using PSI at the Moselle Valley in Germany.…”
Section: Introductionmentioning
confidence: 99%